CENTRAL VERTIGO DUE TO ISCHEMIC STROKE IN A YOUNG WOMAN: A CASE REPORT - Salsabila, Tamara Amanda; Wirathmawati, Andina (Journal of Pain, Headache and Vertigo, 2024)
Background: Vertigo is a symptom that patients often complain about. Vertigo is divided into peripheral and central. One of the causes of central vertigo is ischemic stroke. Ischemic stroke generally occurs in elderly people, but in recent years there has been an increase cases in young people. In addition, the prevalence of stroke is more common in men than women, but recently there has been an increase cases in women. Case summary: A 25-year-old woman presented with sudden vertigo. Physical examination revealed obesity, bidirectional horizontal and vertical nystagmus, left hemiparesis, and hemihypesthesia. Head CT scan showed lacunar infarction in the right basal ganglia and periventricular. The patient was given antiplatelet and vertigo management. Conclusion: Vertigo should be differentiated between peripheral or central vertigo at the emergency department, as it will determine further management. Stroke can occur in young women. Therefore, it is important for clinicians to think about the diagnosis of stroke in patients with vertigo that occur in young women.